Area study: lands of Latin America - Educational Research Council of America. Social Science Staff; Bostick, Nancy (Boston : Allyn and Bacon, 1976)
Discusses the geography, history, customs, people, economics, and government of Latin America and briefly examines the origins of United States' interest in Latin American countries.
includes index.
Keywords: Latin America -- Juvenile literature; Latin America